Assessment of the status of soil organic carbon stocks under natural forest and plantation ecosystems in southern Karnataka - Pradeep; Kumar, K.S. Anil; Avinash, R.K.; Karthika, K.S. (Journal of Plantation Crops, 2020)
A study was conducted to assess the status of soil organic carbon stocks under selected plantation and altered and natural ecosystems in southern Karnataka. Seven locations were identified for the study following the agro-climatic variability. The sites identified were Brahmavara in Udupi (coastal zone), Balehonnur in Chikkamagalur (hilly zone), Madnur and Salegrama in Hassan (northern and southern transitional zone), Alburu in Tumkur (eastern and southern dry zone), Babbur and Javagamatur in Chitradurga (central dry zone). In each of these zones, natural forest ecosystems were assessed in comparison to the plantation-based ecosystems to understand the changes in soil development with emphasis to soil organic carbon (SOC) stocks. The SOC stocks at the surface varied from 1.24 to 6.44 kg m-3 in forests and from 1.53 to 6.51 kg m-3 in different plantation ecosystems. It was found from the study that SOC stocks followed the order hilly zone (per-humid climate) > coastal zone (hot humid climate) > eastern and southern dry zone (moist semi-arid climate) > northern and southern transitional zone (dry sub-humid climate) > central dry zone (dry semi-arid climate). The soils belonged to the order Ultisols and Alfisols. The major taxa of the soils identified at sub-group level of soil taxonomy are Rhodic Kandiustults, Typic Plinthohumults, Ustic Haplohumults, Typic Rhodustalfs, Rhodic Paleustalfs, Kandic Paleustalfs and Typic Haplustalfs.